Exploring Community Engagement: Neighbourhood Infrastructure Evolution in Sentani's Vernacular Settlements - Sarah Cahyadini; Deasy Widyastomo; Purwanita Setijanti; Arina Hayati; Happy R. Sumartinah (Jurnal Penataan Ruang, 2024)
In the era of rapid development, enhancing vernacular settlements is crucial for sustainability, particularly in preserving cultural integrity. The Sentani Tribe exemplifies this challenge with its distinctive cultural heritage deeply rooted in the shores of Lake Sentani. Originally fishermen, the tribe has transitioned to farming, prompting shifts in their settlements and infrastructure. This study focuses on Kehiran villages, where such shifts have necessitated settlement improvements. It investigates opportunities for enhancing vernacular settlements through community engagement, considering cultural adaptations resulting from these infrastructure changes. Through empirical research and analysis, the study follows the identified seven key habitus changes impacting the Sentani Tribe's habitat, influencing infrastructure like worship spaces, schools, roads, and public areas. These findings underscore the potential for participatory improvements in vernacular settlements amidst evolving cultural landscape.